Apokryfer. “Krigshumor” opsamlet af Vilhelm Bergstrøm 1939-45 - Lauridsen, John T. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2016)
John T. Lauridsen: Apocrypha. ‘Krigshumor’ (War humour) collected by Vilhelm Bergstrøm from 1939 to 1945 The article presents and publishes journalist Vilhelm Bergstrøm’s collection of humorous stories from the period 1939–45. The article begins with an argument for the importance of humour in the creation and shaping of public opinion. The structure and tendencies in the 215 stories are examined, and the question is asked if humour had a peak, to which it answers yes – humour peaked in 1941–42. Finally, the article provides an opinion as to which were the most important sources of inspiration for the humour, (daily events) and also accounts for who Bergstrøm’s informants were, first and foremost his network of journalists in Copenhagen.